2016
DOI: 10.1080/21622965.2016.1167497
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Working Memory: Implications for Assessment and Treatment

Abstract: Working memory (WM) impacts a gamut of cognitive abilities, but implicit WM is typically not considered in assessment or treatment, which may explain the variability of results in reviews of WM training. The role of implicit WM in adaptive behavior is reviewed. All we do is action based. Explicit WM plays a major role when we are required to "think"; that is, when we apply previously learned perception-action linkages in new ways to unique situations. Implicit WM is involved in the automation of behavior, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…This confirms that the manipulation of (effortful) cognitive control demands was effective and resulted in two different tasks despite the fact that both tasks used exactly the same stimuli and that the task rules were (theoretically) arbitrary. Limited response selection resources or working memory capacities could supposedly be "used up" by the task demands in case of high cognitive control, so that the beneficial information of the predictive feature is blocked from the response selection stage and thus can no longer impinge on behavior [e.g., Cui et al, 2015;Joyce, 2016]. Most importantly, however, the predictive feature only conveyed an advantage (i.e., improved accuracy) in case of low control demands, but not in case of high control demands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms that the manipulation of (effortful) cognitive control demands was effective and resulted in two different tasks despite the fact that both tasks used exactly the same stimuli and that the task rules were (theoretically) arbitrary. Limited response selection resources or working memory capacities could supposedly be "used up" by the task demands in case of high cognitive control, so that the beneficial information of the predictive feature is blocked from the response selection stage and thus can no longer impinge on behavior [e.g., Cui et al, 2015;Joyce, 2016]. Most importantly, however, the predictive feature only conveyed an advantage (i.e., improved accuracy) in case of low control demands, but not in case of high control demands.…”
Section: Discussionmentioning
confidence: 99%
“…There are two possible explanations for this effect. Limited response selection resources or working memory capacities could supposedly be "used up" by the task demands in case of high cognitive control, so that the beneficial information of the predictive feature is blocked from the response selection stage and thus can no longer impinge on behavior [e.g., Cui et al, 2015;Joyce, 2016]. In case of low control demands, there would however still be capacities left for the exploration of additional available implicit information.…”
Section: Discussionmentioning
confidence: 99%
“…To the extent that working memory is a short-term memory used in service of a task (e.g., a decision followed by a button press), then nearly all adult tasks test both working memory and short-term memory. However, there is growing consensus that working memory may also operate below the level of awareness (Hassin et al 2009;Joyce 2016). This is important for work exploring infant VSTM and may help bridge the gap between infant, toddler, and adult tasks.…”
Section: Short-term Memory or Working Memory?mentioning
confidence: 99%
“…Another important cognitive variable is working memory which is defined as a temporary storage of information that allows information manipulation (Baddeley, 1992). Investigations showed that working memory capacity has a significant effect on conscious learning (Daneman & Carpenter, 1980;Foster et al, 2014;Hitch et al, 2001;Joyce, 2016). As a result, researchers have interested to investigate if SIL could be influenced by working memory (Frensch & Miner, 1994;Janacsek & Nemeth, 2013;Martini et al, 2013;Schwarb & Schumacher, 2009).…”
Section: Introductionmentioning
confidence: 99%